Kultur Apeks untuk Penyediaan Bibit Unggul Tebu Varietas PS864 dan PS881 - Deden Sukmadjaja; Yati Supriyati; Saptowo J. Pardal (Jurnal AgroBiogen, 2014)
In vitro culturetechniques have become alternative to help overcome theproblems those are often encountered in the provision ofseeds through conventional means. Micropropagationthrough apex culture in sugarcane has several advantages,such as the produced plants have higher genetic stability,high multiplication rate, and more healthy seeds (especiallyvirus-free)., The aims of the the research were to produceseeds of two varieties of sugarcane, namely PS864 andPS881, through apex culture. Laboratory-scale research wasconducted at the Indonesian Center for AgriculturalBiotechnology and Genetic Resources Research andDevelopment (ICABIOGRAD), Bogor, while sowing seedsnursery was done in the Experimental Station of Gowa,South Sulawesi Assessment Institute for AgriculturalTechnology. The experiments consisted of initiation andregeneration of apexes, shoots multiplication, rootinginduction, and acclimatization of plantlets. Research resultsshowed the initiation and regeneration of PS864 and PS881through apex culture could be done on MS basic mediumcontaining 0.5 mg/l BAP. Shoot proliferation of both varietiesincreased in the second subculture. Addition of 1 mg/l BAPinto medium in the second subculture resulted in higheraverage number of shoots than that of 5 mg/l BAP, both forPS864 and PS881. Addition of 1 mg/l and 5 mg/l kinetinshowed no significant differences for shoot numberscompared to that of PS864 in medium containing 1 mg/lBAP. The average number of PS881 shoots in multiplicationmedia containing 5 mg/l kinetin was higher than that of 1mg/l kinetin. Increased concentrations of NAA and IBA from0.1 mg/l to 0.5 mg/l in the MS medium were correlated to theincreased number of roots in PS864 shoots. Meanwhile, onlyincreased concentration of NAA that affected rooting percentageof PS881. Acclimatization showed the percentage ofthe plantlets grown in polybags was higher than that directlygrown in planting bed. The primary seeds (G0) produced inthese experiments were ready to be reproduced again toobtain further stages.